2008
DOI: 10.1590/s1516-35982008001100006
|View full text |Cite
|
Sign up to set email alerts
|

Resposta de pastagens perenes à adubação com chorume suíno: cultivar Tifton 85

Abstract: IntroduçãoOs primeiros estudos sobre o uso de dejetos em plantas forrageiras no Brasil foram realizados na Universidade Federal de Santa Maria, em pastagem natural, onde foram obtidos aumentos de até 307% na produção de massa seca (MS) com aplicações repetidas de dejetos (40 m 3 /ha), ao passo que, no centro do País, com aplicações de 150 m 3 /ha/ano, a produção de Brachiaria brizantha cv. Marundu, chegou a 156% a mais em relação à testemunha (Konzen, 2003). Com esse mesmo cultivar, Medeiros et al. (2007) conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
2
7
0
1
Order By: Relevance
“…The same trend was reported for Cynodon spp. fertilized with pig slurry (SCHEFFER-BASSO et al, 2008;VIELMO et al, 2011). The effects found in this study are the same found with mineral N fertilization on grasses, which increases the water concentration, and at higher rates results in progressively greater concentrations of N in the plant tissue (BUXTON & FALES, 1994).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The same trend was reported for Cynodon spp. fertilized with pig slurry (SCHEFFER-BASSO et al, 2008;VIELMO et al, 2011). The effects found in this study are the same found with mineral N fertilization on grasses, which increases the water concentration, and at higher rates results in progressively greater concentrations of N in the plant tissue (BUXTON & FALES, 1994).…”
Section: Resultssupporting
confidence: 75%
“…Este trabalho teve como objetivo avaliar os atributos anatômicos e químicos da grama-missioneira-gigante à aplicação de 0, 62, 124, 186, 248 production and nutritive value of forage grasses (ADELI et al, 2005;SCHEFFER-BASSO et al, 2008;VIELMO et al, 2011). Besides of recognized effect of PS on increasing of forage production, the effects of this N source on anatomical feature are unknown, especially in native forage plants.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen increases the leaf appearance rate and leaf elongation rate, resulting in higher biomass production (GIMENES et al, 2011). SW improved the production of forage DM, confirming its potential as a source of nutrients for pasture (FONSECA, et al, 2007;SCHEFFER-BASSO et al, 2008;VIELMO et al, 2011;KESSLER et al, 2013). , with the maximum FAR occurring in the 675 mL SW pot -1 treatment (Table 3), an increase of 742% compared to the zero dose (0.07 g DM pot -1 day -1 ).…”
Section: Resultsmentioning
confidence: 89%
“…Swine wastewater increases the nutritional value and forage yield of grass pasture systems (FONSECA, et al, 2007;SCHEFFER-BASSO et al, 2008;VIELMO et al, 2011;KESSLER et al, 2013). However, its influence on forage growth dynamics and root development remains unclear, due to variations in the composition and dosage of the applied wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in Brazil, with natural pasture (Durigon et al, 2002;Scheffer-Basso et al, 2008b) and tropical grasses, such as Tifton 85 (Cynodon sp.) (Scheffer-Basso et al, 2008a;Vielmo et al, 2011) and Brachiaria brizantha (Hochst. ex A.…”
Section: Introductionmentioning
confidence: 99%